On the economic policy of import substitution in Russia - K. A. Kolotov (Путеводитель предпринимателя)
A special role in ensuring the accelerated innovative development of the Russian economy is to be played by import substitution in industry, subject to the implementation of its systemic macroeconomic policy, launching mechanisms for the modernization of national reproduction system, the re-creation of competitive elements of global production chains. The author, on the example of international experience of innovative development of industry, considers reproductive mechanisms of the import substitution policy.